A víziók szerepe a változás folyamatában és az élet re-víziója - Balázs SIBA (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2024)
The Role of Visions in the Process of Change and Re-visioning Life. A vision is a possible imagined version of our future. In this essay, we look more generally at the role of hope and vision in our personal change and address the particular path to change that Christianity offers. Human life needs a structured set of goals, where smaller, short-term goals (micro-visions) and larger, long-term goals (big visions) are interlinked. Micro-vision motivates us on a daily basis, while big vision gives our lives long-term direction and meaning. Being able to find the big goals does not only prioritize the smaller ones, the projects of our lives but can also give us a sense of flexibility to let go of the tensions of everyday life, because we can see beyond the days, weeks, years and see the significance of the present in terms of the big picture. The vision of a possible and desired future can give us the strength to withstand the tensions of the present.